2017
DOI: 10.1088/1751-8121/aa677c
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical analysis of dressed photon in ground state of generalized quantum Rabi model using pair theory

Abstract: We consider the generalized quantum Rabi model with the so-called A 2 -term in the light of the Hepp-Lieb-Preparata quantum phase transition. We investigate the dressed photon in its ground state when the atom-light coupling strength is in the deep-strong coupling regime. We show how the dressed photon appears in the ground state. We dedicate this paper to Pavel Exner and Herbert Spohn on the occasion of their 70th birthdays, and Klaus Hepp on the occasion of his 80th birthday.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
(96 reference statements)
0
18
0
Order By: Relevance
“…is obtained in the same way as in Appendix B of Ref. [37]. The mathematical establishment of the adiabatic approximation also says that (∆Φ) 2 ∼ (1 + 4g 2 /ω c )/2ω c as g → ∞ for ε = 0; (∆Φ) 2 ∼ 1/2ω c as g → ∞ for ε = 0.…”
Section: Some Reviews and Our Problemmentioning
confidence: 66%
See 3 more Smart Citations
“…is obtained in the same way as in Appendix B of Ref. [37]. The mathematical establishment of the adiabatic approximation also says that (∆Φ) 2 ∼ (1 + 4g 2 /ω c )/2ω c as g → ∞ for ε = 0; (∆Φ) 2 ∼ 1/2ω c as g → ∞ for ε = 0.…”
Section: Some Reviews and Our Problemmentioning
confidence: 66%
“…As shown in Ref. [37,41], the adiabatic approximation given by Eq. (3.9) is mathematically justified in the following: We define the unitary operator U (g/ω c ) by U (g/ω c ) := σ + σ − D(g/ω c )+ σ − σ + D(−g/ω c ).…”
Section: Some Reviews and Our Problemmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, we note that most previous works have focused solely on the regime where the modulation strength is far less than the modulation frequency [42,45,49,50], allowing for the application of the rotating-wave approximation. On the other hand, there has been recent interest in light-matter interactions in the ultra-strong coupling regime [51][52][53][54][55][56][57], where the RWA is no longer valid. In such ultra-strong coupling systems, it has been shown that topologically protected one-way edge states in dynamic modulation are less susceptible to intrinsic losses [19].…”
Section: A Dynamic Modulationmentioning
confidence: 99%